Wavelet analysis for estimation of mean-curve of impulse waveforms superimposed by noise, oscillations and overshoot. - Satish, L. (IEEE Transactions on power delivery)
This paper describes a novel approach to estimate the mean-curve of impulse voltage waveforms that are recorded during impulse tests. These waveforms in practice are superposed by noise, oscillations, and overshoot. The approach is based on multiresolution signal decomposition (a kind of wavelet transform) and has many advantages over existing methods, since it does not assume any model for estimating the mean-curve, is interactive in nature, suitable for full and chopped impulses, does not introduce distortions due to its application, is easy to implement and does not call for changes to existing standards. Results presented show its applicability